THE EFFECT OF BIOCHAR APPLICATIONS OF RICE HUSK AND COFFEE SKIN ON P AND Zn NUTRITIONS AND THE GROWTH OF RICE (Oryza sativa L.) PLANTS IN SATISFIED RICE LAND - Satber Naibaho (Institute of Computer Science (IOCS), 2021)
This study aims to evaluate the effect of rice husk and coffee husk biochar, evaluate difference effect of rice and coffee husk biochar and to know the effect of difference of dose of rice and coffee husk biochar phosphate and zinc, and rice growth in the paddys soil with high total P . The research was conducted on the greenhouse, Faculty of Agriculture, University of North Sumatra, Medan. The soil which used from the paddys soil in Lubuk Dendang, Perbaungan, Serdang Bedagai which has the high total P. The experiment was carried out using completely randomized design with 7 treatment : control ; 10 tons/ha, 20 tons/ha, and 30 tons/ha rice husk biochar ; 10 tons/ha, 20 tons/ha, and 30 tons/ha coffee husk biochar. The Analysis of data used the analysis of variance and contrast orthogonal test.